PENCEGAHAN TINDAK PIDANA PENCUCIAN UANG MELALUI MITIGASI RISIKO PADA BANK MUAMALAT CABANG MEDAN BALAIKOTA - Lisa Andriansyah Rizal; Sunarmi Sunarmi; Mahmud Mulyadi; Suhaidi Suhaidi (USU LAW JOURNAL, 2017)
ABSTRACT Risk mitigation is a form of systematic methodology used by senior management in order to reduce organizational risk. the banking industry is an industry that cannot be avoided from risk, therefore the implementation of risk management is very important in order to provide smooth business of the bank itself. There are several risks in the banking industry, which are credit, market, liquidity, operational, legal, reputation, strategic and compliance risks. Risk mitigation to prevent money laundering in Muamalat Bank branch of Medan Balai Kota is done by supervision in special work unit, applying know your costumer, verification and monitoring. Keywords : Risk mitigation, money laundering